Filsafat Lingkungan dan Pendidikan Sains: Eksplorasi Pengetahuan Lokal, Metakognitif, dan Keadilan Ekologis Suku Anak Dalam di Tengah Ekspansi Sawit dan Kopi Jambi: Environmental Philosophy and Science Education: Exploring Local Knowledge, Metacognition, and Ecological Justice of the Anak Dalam Tribe Amidst Palm Oil and Coffee Expansion in Jambi - Ardi Mustakim; Rayandra Asyhar; Asrial Asrial; Syaiful Syaiful; Revis Asra; Nizlel Huda; Elvaro Islami Muryadi (Jurnal Filsafat Indonesia, 2026)
Oil palm expansion in Jambi has generated ecological, social, and epistemological crises affecting the marginalization of the Suku Anak Dalam (SAD). This study examines the issue through environmental philosophy and science education by positioning Indigenous knowledge as a foundation for ecological justice. The research employed a qualitative-critical approach through philosophical analysis, literature review, and ethnographic perspectives. Findings reveal that oil palm expansion not only causes deforestation and biodiversity loss but also erodes Indigenous ecological knowledge systems. In contrast, Jambi coffee agroforestry represents a harmonious relationship between humans and nature that supports environmental sustainability. The study emphasizes that integrating local knowledge, metacognitive values, and environmental ethics into science education can foster ecological awareness, critical thinking, and students’ moral responsibility. Philosophically, this research contributes to strengthening science education grounded in ecological justice and epistemic pluralism in the Anthropocene era.